(3aQOhS GdCNHGQ HeCKhQ GdNWGH GdeNQL Ydi cJGH GdTgGHs - (3CHh TLGY TjQhjg Hf TgQOGQ Hf TjQhjg Hf afGNSQh GdgeOGfi GdOjdeis; (3GdbVGYj , TgGH GdOjf CHh YHO Gddg eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj,J (B454 (3g` s ((3SGde GdebQi Hf fHgGf Hf efjY Hf SGQjI s)
(3ChdgG (B:s
(3jHJOF HCKfGA MOjK CdG CNHQce HCaVd OQLI GdUjGe hGdUObI hGdUdGI UdGM PGJ GdHjf s
(3BNQgG (B:s
(3SejJ ZehSkG dZeSgG UGMHgG ai GdGKe Ydi fHjI GdeSJMda BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1254s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs